2021
DOI: 10.1186/s12911-020-01360-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of IT-based interventions on self-management in adult kidney transplant recipients: a systematic review

Abstract: Background Kidney transplant outcomes are broadly associated with transplant recipients’ capacity in following a complex and continuous self-management regimen. Health information technology has the potential to empower patients. This systematic review aimed to determine the impacts of IT-based interventions for self-management in kidney transplant recipients. Methods A comprehensive investigation was performed in MEDLINE (via PubMed) and EMBASE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
(59 reference statements)
1
10
0
2
Order By: Relevance
“…Among IT-based solutions, e-health programs or telemedicine-based interventions are more effective than other solutions. Our results are consistent with previous studies that examined the positive effect of IT-based interventions on transplantation in specific organ transplantations [71,73]. Our investigation showed that non-electronic educational resources should be used alongside other IT-based interventions to promote patient self-care to be more effective and applicable.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among IT-based solutions, e-health programs or telemedicine-based interventions are more effective than other solutions. Our results are consistent with previous studies that examined the positive effect of IT-based interventions on transplantation in specific organ transplantations [71,73]. Our investigation showed that non-electronic educational resources should be used alongside other IT-based interventions to promote patient self-care to be more effective and applicable.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies (72.5%) showed that developed programs and applied solutions had a statistically significant positive impact on the ability of transplanted patients to his/her self-management. In the same way, there is a growing body of evidence regarding the positive results of self-management programs in chronic diseases to enhance a person's ability to cope with his/her situation and better management of his/her disease [6,40,71].…”
Section: Discussionmentioning
confidence: 99%
“…Such multidisciplinary work has been previously recommended [ 39 ]. Alternative strategies have included digital intervention which has shown some promising improvements in self-management [ 45 ], however, adolescent, and young adult kidney transplantation groups require further investigation [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This drug training should start from the pre-transplant period and continue in the long term postoperatively. The training aims to eliminate patients' lack of knowledge, correct their mistakes, help them adapt to the post-disease process, and help them comprehend the key points [22][23][24]. Moors-Tielen et al (2008) report that 40% of kidney transplant patients stated that forgetting to take their immunosuppressive drugs would not cause serious problems.…”
Section: Tacrolimus Levelsmentioning
confidence: 99%